(untitled) (Development Service Industry Management, 2025)
The article reveals the main aspects of enhancing the competitiveness of restaurants in Zakarpattia through the implementation of effective models and approaches. It is established that successful competitiveness improvement depends on the use of innovative strategies, particularly adapting global practices to local conditions. It is clarified that important components include the use of digital technologies, the development of gastronomic brands, the popularization of local cuisine, and a customer-oriented approach. The significance of innovations, such as online table reservations and mobile apps for ordering, is emphasized as they contribute to service convenience. It is highlighted that the integration of innovations into marketing strategies, such as promotions, loyalty programs, and themed events, allows restaurants to attract new customers and retain loyal ones. It is stated that a crucial element of success is the creation of an authentic gastronomic experience through the use of local products and seasonal changes in the menu. It is determined that restaurants actively use social media and online platforms for customer interaction, enhancing their popularity and recognition. It is noted that adaptation to environmental requirements and sustainable development are additional factors contributing to the competitiveness of establishments. The importance of high-quality service is also disclosed, particularly through regular staff training, which ensures customer satisfaction and builds a strong restaurant image. It is established that the analysis of effective approaches to enhancing the competitiveness of Zakarpattia restaurants demonstrates the importance of a comprehensive approach, including marketing, service, innovation, and environmental practices. It is clarified that the further development of this market requires the improvement of the use of cutting-edge technologies, service optimization, and adaptation to changing market conditions. It is emphasized that recommendations for improving the competitive strategy of the restaurant business in Zakarpattia should take into account trends at the national and international levels. It is highlighted that achieving sustainable development for restaurant enterprises requires constant adaptation and innovation.